(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
A simple, sensitive and rapid spectrophotometric method for determination of Montelukast Sodium (MON) in both pure form and pharmaceutical formulations was developed. This method was based on the oxidation of the studied drug in presence of acidic medium by a known excess of (Potassium bromide: Potassium bromate) (KBr:KBrO3) and subsequent determination of unreacted oxidant by reacting it with Crystal Violet (CV) dye [4 [bis [4 (dimethylamino) phenyl] methylidene] cyclohexa-2,5-dien-1-ylidene]-dimethylazanium to produce blue product at λmax. 592 nm. The linearity range was found to be (5-50)µg/ml and molar absorptivity 1.5691×104 L/mol.cm, correlation coefficient 0.9993 and the limit of detection 0.209 µg/ml. This method was successfully applied for the determination of (MON) in tablet formulation.